Comparison of the relationship between cosmology and political thought in ancient Iran and ancient Greece. - Behrooz Dailam salehi (رهیافتهای سیاسی و بین المللی)
We know that political thought in Iran and the West has grown in two different contexts. In Iran, political thought is in the context of religious cosmology and in the West, in the context of philosophical cosmology. Many of the differences between Iranian and Iranian-Islamic political thought on the one hand and Western political thought on the other hand are rooted in this different background in the growth and development of thought. The main goal of this research is to scrutinize this relationship by focusing on the nature of the difference between these two platforms, relying on the formation of two different cosmologies, one of which we call Iranian cosmology and the other Western cosmology. The hypothesis that is tested in the research is that the two currents of Iranian and Greek cosmology entered different paths from the beginning of their emergence and expansion, and along with them, they advanced the growth and evolution of political thought in different paths: one of the path of religious cosmology and the other in the path of philosophical cosmology. The result is that from these two paths, philosophical cosmology has been more capable of transformation and more possibility for the development of political thought. In addition, the research method is content analysis.